Design and Validation of Dynamic Fluid Experiment Devices as a Media of Physics Learning - Suhartiwi, Fenny; Mariyo, Hadis; Aryani, Dila Rizki (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Media usage of teaching in schools very important role for students and can assist students in the learning process and can improve student learning outcomes. This research aims to design build and validate device of fluid dynamic experiment as learning media of physics in school. The subject of this research is an experimental device consisting of experimental tools and manuals. Data collection using a validation assessment sheet provide to a validator consisting of five people. Data were analyzed descriptively to determine the result and the value of its validity. The results of data analysis obtained from the assessment of validation that is, in the experimental tools and manuals got average score 3.46 and 3.60 with very high category. The dynamic fluid experimental device has been declared valid, resulting in an experimental device that is eligible to be used as a media of physics learning in school.